2008
DOI: 10.1017/s0003598x0009774x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling maritime interaction in the Aegean Bronze Age

Abstract: The authors raise spatial analysis to a new level of sophistication -and insight -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 19 publications
(13 reference statements)
0
87
0
5
Order By: Relevance
“…Of course similar links have been made between geographical locations and the role of sites in history: Delos in the case of Davis (1982) and Knossos in the case of Knappett et al (2008). However, in the latter case, the modeling also suggested that a pair of candidates, Knossos and Malia, had these spatial advantages, again compatible with the uncertainties in modeling.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Of course similar links have been made between geographical locations and the role of sites in history: Delos in the case of Davis (1982) and Knossos in the case of Knappett et al (2008). However, in the latter case, the modeling also suggested that a pair of candidates, Knossos and Malia, had these spatial advantages, again compatible with the uncertainties in modeling.…”
Section: Resultsmentioning
confidence: 63%
“…This context was chosen so that we can illustrate general methodological principles with a practical archeological example, with the added benefit that it allows us to make direct contact with the classic work of Wilson (1987, 1991). The last decade has seen a rise in the use of such modeling techniques on settlement patterns in a wide range of times and other places: Crete in the second millennium BC (Bevan and Wilson, 2013) or the Middle Bronze Age (Evans et al, 2006;Knappett et al, 2008Knappett et al, , 2011Paliou and Bevan, 2016), Iron Age NE Syria (Davies et al, 2014), early second millennium BC Central Anatolia (Palmisano and Altaweel, 2015), late first Millennium Latenian urbanization (Filet, 2017), early Japan (Mizoguchi, 2009), the Maya lowlands (Ducke and Kroefges, 2008), to give just a few examples. Similar methods can be used when modeling of other types of spatial organization, such as lithic assemblages (Wilson, 2007) to name just one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been shown to be particularly useful in studies of regional interaction (Knappett 2013b) and especially larger-scale spatial analyses, for instance in studies of long-distance trade and contacts, centrality and (proto-) urbanism (Fulminante 2012; Knappett et al 2008;Sindbaek 2007;Riede 2014). In archaeology, these fields have a longer tradition of using the term network to describe larger-scale interaction spheres such as trade networks and political networks.…”
Section: Identity From a Network Perspectivementioning
confidence: 99%